Mg and Si isotopic fractionation patterns in types B1 and B2 CAIs: Implications for formation under different nebular conditions. (30th July 2013) - Bullock, Emma S.; Knight, Kim B.; Richter, Frank M.; Kita, Noriko T.; Ushikubo, Takayuki; M Pherson, Glenn J.; Davis, Andrew M.; Mendybaev, Ruslan A.
Abstract: Magnesium and silicon isotopic profiles across melilite grains in two type B1 and two type B2 calcium‐aluminum‐rich inclusions (CAIs) reveal differing but constant enrichments in heavy isotopes everywhere except ≤1000 μm from the CAI margins. There is no close correlation in the B1s or the B2s between isotopic composition and åkermanite content of the melilite, a measure of progressive igneous crystallization, yet such a correlation might be expected in a type B2: without a melilite mantle (as in B1s) to seal the interior off and prevent further evaporation, the melt would have maintained communication with the external gas. These observations indicate a model in which B1s and B2s solidified under differing conditions. The B2s solidified under lower hydrogen pressures ( P H 2 ≤ 10 −4 – 10 −5 bars) than did B1s ( P H 2 > 10 −4 bars), so surface volatilization was slower in the B2s and internal chemical and isotopic equilibrium was maintained over the interval of melilite crystallization. The outermost zones of the CAIs (≤1000 μm from the edge) are not consistently enriched in heavy isotopes relative to the interiors, as might be expected from diffusion‐limited surface evaporation of the melt. In all cases, the magnesium in the CAI margins is lighter than in the interiors. In one case, silicon in the margin also is lighter, but locally in some CAIs, it is isotopically heavier near the surface. If melt evaporation played a role in the formation of these outer zones, a later event in many cases caused isotopic re‐equilibration with an external and isotopically near‐normal reservoir.